ONLINE DIGITAL FLIPBOOK MODULE: AN ALTERNATIVE TEACHING MATERIAL IN THE 21st CENTURY - Oktha Ika Rahmawati; Fitri Nurdianingsih; Andri Andri (PROJECT (Professional Journal of English Education), 2023)
Online module can be one of the solutions as teaching material in this modern era. This study is descriptive qualitative study. It aims to explain the implementation of online module and students’ responses toward it. The module was developed using online application heyzine.com and the material was about sentence structure.  The students were asked to read it and give responses about it. Digital Flipbook module can be implemented successfully in learning process and the students in conclusion can give positive responses toward the implementation of it in the classroom. Keywords:  Digital Flipbook; Module; Teaching Material